Productivity and nutritional value of African Star managed with different leaf blade mass (Acta Scientiarum. Animal Sciences, 2016)
Pasture management with levels of leaf blades may favor significant increase in production, and the leaves indicated an important role in plant-animal relationship, caused by photosynthesis efficiency and better quality in animal diet. Current study identifies which leaf blade mass of the African star (Cynodon nlemfuensis var. Nlemfuensis) provides better productivity and nutritional value. Treatments comprised different leaf blade masses: 800, 1200, 1600 and 2000 kg of dry matter ha-1. The experimental design was completely randomized, with four treatments and three repetitions, totaling 12 plots with 100 m2 each. Results indicated increase in production, in the leaf/stem ratio and in the interval days according to increase in leaf blade mass. Daily accumulation rate was similar to treatments. Crude protein decreased and fiber increased with rise in leaf blade mass and the highest forage productions were reported in the treatments 1200 and 1600 kg ha-1 leaf blade mass.